The Improvement of Students’ Information Literacy-based on the Association of College and Reseach Libraries (ACRL) using Empowering 8 - Alpin Herman Saputra (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
The result of a preliminary study conducted by the researcher showed that the information literacy of students at the Elementary School Teacher (PGSD) Program was low. Therefore, this research was done to understand the effect of Empowering 8 model application in improving studentsÃ¢â‚¬â„¢ information literacy. This research used the quasi-experimental method with a pretest-posttest control group design. The research participants were 66 students, consisting of 33 students in the experimental class and 33 students in the control class. This research utilized some instruments, including pretest, posttest, questionnaires and observation sheets. The results obtained were: the studentsÃ¢â‚¬â„¢ information literacy ability based on ARCL experimental class was in the high category. It revealed that application of Empowering 8 model had a positive effect on the studentsÃ¢â‚¬â„¢ information literacy.Ã‚Â